1994
DOI: 10.1002/ceat.270170207
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous catalytic methylation of catechol

Abstract: It has been shown that, after a partial deactivation, y-alumina ( y-A1203) is a good catalyst for selective methylation of 1,2-benzenediol in the temperature range of 260 -310 "C. The main products are the desired 3-methyl-I ,2-benzenediol and 2-methoxyphenol, which may be converted in another step into 3-methyl-I ,2-benzenediol, giving an overall selectivity for the desired products of 80 to 90%. The catechol forms a strongly chemisorbed surface species on y-alumina and its steric adsorption model correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Isotopic studies have confirmed that the O-H bond was broken during adsorption of methanol on the alumina surface [1,36]. Consequently, methanol makes a covalent bond with the surface of g-alumina with the release of one water molecule, as shown by IR measurements [1,2,36]. Consequently, we assumed, in our calculation, that a previous deprotonation of methanol happens, leading to the formation of a water molecule, and this step is not considered here.…”
Section: Adsorption Of Methanol On the Alumina Clustermentioning
confidence: 99%
See 3 more Smart Citations
“…Isotopic studies have confirmed that the O-H bond was broken during adsorption of methanol on the alumina surface [1,36]. Consequently, methanol makes a covalent bond with the surface of g-alumina with the release of one water molecule, as shown by IR measurements [1,2,36]. Consequently, we assumed, in our calculation, that a previous deprotonation of methanol happens, leading to the formation of a water molecule, and this step is not considered here.…”
Section: Adsorption Of Methanol On the Alumina Clustermentioning
confidence: 99%
“…According to Busca et al [36], several chemisorbed species may be found, depending on temperature, one of them corresponding to a bidented species with the OH group of methanol bound to aluminum and oxygen surface atoms. Finally, in the experimental conditions reported by Porchet et al [2][3][4], methanol mainly adsorbs as a bidented species on g -alumina, i.e. corresponding to this species of Busca et al Methanol deprotonation by a basic hydroxyle of the surface involves water formation and Porchet et al have shown that this occurs during the adsorption.…”
Section: Adsorption Of Methanol On the Alumina Clustermentioning
confidence: 99%
See 2 more Smart Citations
“…The formation rate of 4-methylcatechol is slow compared to the production rates of the other species which is favourable because it is an undesired stable product. On the other hand guaiacol is itself a methylation agent: it decomposes in a reverse reaction to catechol and methanol or can be transformed by rearrangement to the desired 3-methylcatechol (Porchet et al, 1994). Therefore the overall yield Y2 shows the typical reaction path of an intermediate product.…”
Section: Integral Reactormentioning
confidence: 99%